PENDAPATAN USAHATANI BAYAM DI DESA CIARUTEUN ILIR KECAMATAN CIBUNGBULANG KABUPATEN BOGOR JAWA BARAT - Pratica Dewi; Anna Fariyanti (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2015)
Spinach as an economic crop is known as the king of vegetables and loved by the whole society. The purpose of this research was to analyze spinach farm income, level of farm efficiency, return to labor and return to capital. The data were analyzed using descriptive statistic methods, farm income analysis, and R/C ratio using a sample of 30 large-scale farmers and 30 small-scale farmers. The result showed that the income of large-scale farmers were greater than that of small-scale farmers in dry (September-October 2013) and rainy (February-March 2014) cropping season. Meanwhile, the income of small-scale and large-scale farmers in the rainy season was higher than in the dry season because of the high price of spinach. R/C ratio of spinach farming was greater than one. The R/C ratio indicated that spinach farming was efficient. Based on the return to labor and return to capital, it can be concluded that the farmers´decision to grow spinach in Ciaruteun Ilir Village was right.Farmers should be responsive to the growing season and the creation of value-added spinach, and the plastic hood should be made to protect the spinach plants from pests and diseases.